Pumping scheme optimisation of 980-nm pumped L-band EDFA associated with broadband noise as the secondary pump - Adikan, Faisal Rafiq Mahamd; Noor, A.S.M.; Mahdi, M.A. (2004)
L-band gain improvement through usage of secondary pumping sources in the form of broadband noise (amplified spontaneous emission, ASE) is conducted. For an L-band amplifier system employing ASE to improve gain, pumping the system counter-directionally with ASE while the 980-nm pump is being used in a co-propagating configuration would yield the best overall performance in terms of gain and noise figure. For high power applications, the 980-nm and ASE sources must be counter-directionally pumped to the direction of the L-band signal. Gain improvement of 1570-nm signal in between 6 and 8.5 dB is attained at 12 mW of 980-nm pump laser. (C) 2004 Elsevier B.V. All rights reserved.